Unveiling the Potential of AI Assistants: A Review of AI in Building Materials Selection - Andi Prasetiyo Wibowo (Journal of Artificial Intelligence in Architecture, 2024)
Fast-advancing Artificial Intelligence (AI) has transformed many industries, including construction. AI offers innovative solutions to increase efficiency and effectiveness in various aspects of construction, one of which is selecting building materials. By reading relevant literature, this study aims to determine how much AI can help choose building materials so that projects go more easily and quickly. Using SCOPUS as its principal database, this study conducted a literature review. The method of this study begins with the process of filtering articles using the key string: ("artificial intelligence" OR AI) AND ("building materials" OR "construction materials") AND ("efficiency" OR "time" OR "cost") to find relevant articles. The research results show that AI can help improve time and cost efficiency in selecting building materials through various means, such as data analysis, material recommendations, cost optimisation, and performance estimation. In conclusion, this study shows that AI has much potential to make choosing building materials more efficient and effective, thus reducing building time, costs, and environmental damage. Still, it also dramatically impacts building monitoring and maintenance and task automation.